Local Cultural Wisdom of Natural Disaster-Prone Communities in Probolinggo, Indonesia (Socio-Religious Perspective) - Aminkun Imam Rafii; Sarmini Sarmini; Sukma Perdana Prasetya; Dock Chanthoeurn (Universitas Islam Negeri Walisongo Semarang, Indonesia, 2023)
Values education can be realized by re-empowering existing local wisdom in accelerating the handling of disaster mitigation in Probolinggo Regency. This study explores local cultural knowledge from a religious perspective as a form of community adaptation to natural disasters in the Probilonggo area. This research is descriptive qualitative research using analytical techniques from Miles Huberman. Data collection techniques through interviews, observation, and documentation of data sources, namely BPBD East Java Province, BPBD Probolinggo Regency and community leaders who are in the Mount Bromo disaster-prone area, Probolinggo Regency, and other parties related to the research focus. The results of data analysis concluded that the local cultural wisdom of the Tengger people relies on religion and beliefs such as the wingsuit, shamans, and several religious ceremonies such as Kasada, Karo, Unan-Unan, Kapat, Kawulu, Kasanga, Sengkolo contain some positive values in overcoming disasters and maintaining a harmonious relationship between God, humans, and the natural environment. The people of Tengger still uphold the importance of local cultural wisdom in overcoming disasters through the philosophy of